The Effect of Application Anemia Management Module On Improving Maternal Behaviors and Hemoglobin Level among Pregnant Women with Anemia - Irma Nadziroh; M. Choiroel Anwar; Sudirman Sudirman (International Journal of Nursing and Health Services (IJNHS), 2020)
Lack of knowledge of mothers on the importance of iron tablet consumption impact on compliance. So that the iron requirement is not fulfilled and the effect of anemia. Countermeasures to raise awareness and behavior to increase hemoglobin levels. Educational modules consisted of information regarding pregnancy and the importance of anemia Fe tablet consumption. The study aimed to examine the effect of the anemia management module to change mothers' behavior in improving hemoglobin levels. A quasi-experimental study pretest-posttest with a non-equivalent control group was applied in this study, with a purposive sampling technique, where the intervention and control groups, respectively, 14 people. The data were analyzed using an independent t-test. Furthermore, to determine the effect of continued modules using linear regression. The intervention effect on knowledge, attitudes, actions by the p-value of 0.00, but it does not directly influence HB's p-value 0.231 (> 0.05). With its application for 30 days with biweekly visits, the anemia management module effectively changes the mother's behavior to improve knowledge, attitudes, actions, and modules that do not directly influence Hb's increase. Use of the anemia management module as companion media education of health workers, especially in the range of PHC